Plant-based default nudges effectively increase the sustainability of catered meals on college campuses: Three randomized controlled trials - Boronowsky, Renate D.; Zhang, Angela W.; Stecher, Chad; Presley, Kira; Mathur, Maya B.; Cleveland, David A.; Garnett, Emma; Wharton, Christopher; Brown, Daniel; Meier, Adam; Wang, May; Braverman, Ilana; et al. (Frontiers in Sustainable Food Systems, 2022)
Background Literature suggests limiting consumption of animal products is key to reducing emissions and adverse planetary impacts. However, influencing dietary behavior to achieve planetary health targets remains a formidable problem. Objective We investigated the effect of changing the default meal option at catered events–from meat to plant-based–on participants' meal choices using three parallel-group, balanced, randomized controlled trials (RCT), and use these experimental results to project differences in plant-based default vs. meat default events on greenhouse gas emissions (GHGEs) (kg CO2 − eq), land use (m2), nitrogen (g N), and phosphorus (g P) footprint. Methods Data collection was performed at three catered events (n = 280) across two college campuses. The selected experimental sites used convenience sampling. Events consisted of a graduate orientation, sorority dinner, and academic conference. Eligibility of individual participants included being 18 years or older and an invitation to RSVP for an enrolled event. Participants were randomly assigned to one of two groups: the control group received a RSVP form that presented a meat meal as the default catering option; whereas the intervention group received a form that presented a plant-based meal as the default. The primary outcome of interest in each group was the proportion of participants who selected plant-based meals. To explore environmental impacts, we modeled the footprints of four hypothetical meals. Using these meals and RCT results, the impact (GHGE, land use, nitrogen, phosphorus) of two hypothetical 100-person events was calculated and compared. Results In all, participants assigned to the plant-based default were 3.52 (95% CI: [2.44, 5.09]) times more likely to select plant-based meals than those assigned to the meat default. Using these results, a comparison of hypothetical events serving modeled meat-based and plant-based meals showed a reduction of up to 42.3% in GHGEs as well as similar reductions in land use (41.8%), nitrogen (38.9%), and phosphorus (42.7%). Conclusion Results demonstrated plant-based default menu options are effective, providing a low-effort, high-impact way to decrease consumption of animal products in catered events. These interventions can reduce planetary impact while maintaining participant choice.